MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPS MATERI PRANATA SOSIAL MELALUI MODEL PEMBELAJARAN JIGSAW PADA KELAS VIII D MTSN BANJAR SELATAN 1 BANJARMASIN - Sri Umiyati (JURNAL SOCIUS, 2013)
This classroom action research is done based on the condition in the social science subject, specifically at class eight D of State Junior Islamic School 1 of  South Banjarmasin. It showed that the students’ had low achievement and did not reach the minimum completeness of study determined by the school, namely 75. This study is used action research method to increase the students’ achievement. It is expected that students no longer feel bored in learning social science subject and more active in discussion; therefore, the teacher is not the only source for learning. In this classroom action research, the researcher used two cycles. The first cycle consisted of two meetings and second cycle done in only one meeting. The data collection used were observation sheet for both teacher and students, written test, and questionnaire for students only. Based on the findings and discussion, it can be concluded that: (1) the students’ activities  by using Jigsaw model have increased; (2) the students learning outcomes have also increased and they were above the completeness of classical learning, namely 94,8%; (3) the students’ respond toward the use of Jigsaw  showed that the students were interested in learning by Jigsaw model.  In conclusion, it is expected  that the teachers apply Jigsaw as one of alternatives in teaching social science subject, for the students find this model attractive as well as interesting one; therefore, they do not feel bored and can increase their learning outcomes.Keywords: Activity, Learning Outcome, Social Science Subject, Jigsaw Model